Subjective and Objective Actigraphic Sleep Monitoring and Psychopathology in a Clinical Sample of Patients with Night Eating Syndrome, with and Without Binge Eating Behaviors - Orna, Tzischinsky; Yael, Latzer; Miri, Givon; Orna, Kabakov; Sigal, Alon; Nehama, Zuckerman-Levin; Michal, Rozenstein-Hason (Journal of Sleep And Sleep Disorder Research, 2015)
Introduction: Night Eating Syndrome (NES) is a phenomenon combining aspects of both sleeping disorders and Eating Disorders (EDs). To the best of our knowledge, few studies to date have examined NES among patients with EDs. None examined ED patients with and without NES in clinical settings by comparing their sleep disturbances using the new NES diagnostic criteria 1. This study aimed to compare subjective and objective sleep patterns and ED-related psychopathology among NES patients with and without binge eating (BE) behavior. Method: The sample included 71 women, ages 19-62, referred for assessment to a hospital Eating Disorders Clinic. Measures included self-report questionnaires, psychiatric evaluation and actigraph recording for one week. Participants were divided into three subgroups: those with NES without BE behavior (NES-only, n = 17), with both NES and BE behavior (NES-BE, n = 22), and with BE behavior without NES (BE-only, n = 32). Results: Regarding objective sleep monitoring, only one group difference emerged: significantly longer sleep duration for the NES-only group than the other groups. Subjectively, both NES-only and NES-BE groups described significantly more sleep disturbances than the BE-only group. Moreover, only one inter-group difference emerged in ED-related psychopathology: According to new NES diagnostic criteria, the NES-only and NES-BE groups reported significantly higher levels of NES symptoms than the BE-only group. Conclusions: Groups' similarities in sleeping disturbances and psychopathology level and differences between objective and subjective sleep disturbances raise the question of whether NES should be considered part of the BE-only subgroup, calling for further research.
Keywords: night eating syndrome; eating disorders; binge eating; actigraph; sleep-wake cycle.